First:
2x + 2z = 4
2(x+z)=4
x+z=4/2
x=2-z
-x - y - z= -8
-(2-z)-y-z= -8 replace x
-2+z-y-z= -8 (cancel z)
-2-y= -8
6 = y
Then:
-4x + 4y + 5z = 7 replace x and y
-4(2-z)+4*6 + 5z = 7
-8 + 4z + 24 + 5z = 7
16 + 9z = 7
9z = 7 - 16
9z = -9
z = -9/9
z= -1
Finally
x= 2-z replace z
x = 2- (-1)
x = 3
Answer:
Step-by-step explanation:
u do 5 times x then do 1 times f .
Answer:
Mean: 5, Median: 5, Mode: 5, Range: 4
Step-by-step explanation:
Mean: 5
5 + 4 + 6 + 3 + 7 + 5 = 30
30/6 = 5
Median: 5
3, 4, 5, 5, 6, 7,
Mode: 5
3, 4, 5, 5, 6, 7
2 fives
Range: 4
7 - 3 = 4
Answer:
Option C, 30
Step-by-step explanation:
<u>Step 1: Identify how many people spent $200</u>
There was only 30 people that spent $200
Answer: Option C, 30